2018
DOI: 10.15406/jbmoa.2018.06.00220
|View full text |Cite
|
Sign up to set email alerts
|

Feed potentials of Saccharomyces cerevisiae biomass cultivated in palm oil and cassava mill effluents

Abstract: Saccharomyces cerevisiae biomass is one of the microbes of food safety. In animals, Saccharomyces cerevisiae in their diets are known to play several vital roles including prevention of diarrhea and mortality, boosting of immune system, performance, milk production, fiber degradation and nutrient digestability, adsorption of toxic metal such as cadmium, stabilization of rumen pH and microorganisms. Saccharomyces cerevisiae have been widely cultured in several waste feedstocks' including cassava and palm oil mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…There is the need for utilization in several other fields through biotechnological advances. Some of the area that cassava based products have demonstrated positive effect for sustainable management practices including energy production viz: bioethanol [35,[41][42][43], biogas [44][45][46][47][48], bio-electricity using microbial fuel cells technology [49][50][51][52][53]; animal feed production [22,26,54], bio-surfactants [55], raw materials for production of amino acids [26], enzymes [56,57], organic acids etc. The conversion of the potential cassava mill effluents to bio-valued products could create employment for several families especially in region of high cassava production.…”
Section: Estimation Of Future Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…There is the need for utilization in several other fields through biotechnological advances. Some of the area that cassava based products have demonstrated positive effect for sustainable management practices including energy production viz: bioethanol [35,[41][42][43], biogas [44][45][46][47][48], bio-electricity using microbial fuel cells technology [49][50][51][52][53]; animal feed production [22,26,54], bio-surfactants [55], raw materials for production of amino acids [26], enzymes [56,57], organic acids etc. The conversion of the potential cassava mill effluents to bio-valued products could create employment for several families especially in region of high cassava production.…”
Section: Estimation Of Future Scenariomentioning
confidence: 99%
“…This could be due to its toxicity level. Several toxicant have been reported in cassava mill effluents including cyanides [23], heavy metals [24], acidic pH [34][35][36], high concentration of chemical oxygen demand, anions (sulphate, nitrate, phosphate), salinity, total dissolved solid, conductivity, turbidity, etc [25]. The toxicity of the effluents may be highly influenced by the cyanide content, acidic pH and heavy metals content.…”
Section: Introductionmentioning
confidence: 99%
“…Another bacterium, Lactobacillus bulgaricus is essential in human diet because of its role in yoghurt production. These two microbes are typical example of grass organisms that have implicated with food safety [7].…”
Section: Introductionmentioning
confidence: 99%
“…Reethus et al [3] reported that Saccharomyces cerevisiae is mainly used in animal, while Saccharomyces boulardii is the most commercially used probiotics (a live microbial feed supplemented to animal diets to enhance the balance of microbes found in the intestines). Saccharomyces cerevisiae are widely used in fermentation processes of sugar rich substances such as cassava wastes [4,5], grapes, sugarcane, fruit wastes [3].…”
Section: Introductionmentioning
confidence: 99%